Families Apart : Migrant Mothers and the Conflicts of Labor and Love - Pratt, Geraldine (Book collections on Project MUSE., 2012)
In a developing nation like the Philippines, many mothers provide for their families by traveling to a foreign country to care for someone else's. Families Apart focuses on Filipino overseas workers in Canada to reveal what such arrangements mean for families on both sides of the global divide. The outcome of Geraldine Pratt's collaboration with the Philippine Women Centre of British Columbia, this study documents the difficulties of family separation and the problems that children have when they reunite with their mothers in Vancouver. Aimed at those who have lived this experience.